High Hereditary Transthyretin-Related Amyloidosis Prevalence in Crete: Genetic Heterogeneity and Distinct Phenotypes. (9th October 2022) - Tzagournissakis, Minas; Foukarakis, Emmanouil; Samonakis, Dimitrios; Tsilimbaris, Miltiadis; Michaelidou, Kleita; Mathioudakis, Lambros; Marinis, Anastasios; Giannakoudakis, Emmanouil; Spanaki, Cleanthe; Skoula, Irene; Erimaki, Sofia; Amoiridis, Georgios; et al.
Abstract : Background and Objectives: Our goal was to study hereditary transthyretin-related amyloidosis (hATTR) in Crete, Greece. Methods: We aimed at ascertaining all hATTR cases in Crete, an island of 0.62 million people. For this, we evaluated patients with polyneuropathy, autonomic involvement, cardiomyopathy, and/or ophthalmopathy suggestive of hATTR, who presented to the physicians of this study or were referred to them by other physicians. Genetic analyses were performed on all patients suspected of suffering from hATTR. We included in our observational longitudinal cohort study all individuals, residents of Crete, who, during the study period (1993–2019), were found to carry a pathogenic TTR variant. Results: Over the past 27 years, 30 individuals (15 female patients, 15 male patients), from 12 apparently unrelated families, were diagnosed with hATTR, whereas evaluation of their offspring identified 5 asymptomatic TTR pathogenic variant carriers. The most prevalent TTR variant detected was p.Val50Met, affecting 19 patients (11 female patients, 8 male patients) and causing a rather consistent phenotype characterized by predominant polyneuropathy of early adult onset (median age of symptom onset: 30 years; range: 18–37 years). Specifically, patients affected by the p.Val50Met TTR variant experienced progressive sensorimotor disturbances, involving mainly the lower extremities, associated with autonomic and/or gastrointestinal dysfunction. The second most frequent TTR variant was p.Val114Ala, found in 10 patients (4 female patients, 6 male patients) who were affected at an older age (median age of symptom onset: 70 years; range: 54–78 years). This variant caused a predominantly cardiomyopathic phenotype, manifested by congestive heart failure and associated with peripheral neuropathy, carpal tunnel syndrome, and/or autonomic involvement. In these patients, cardiac amyloid deposition was detected on 99m-technetium pyrophosphate scintigraphy and/or heart biopsy. The third TTR variant (p.Arg54Gly) was found in a 50-year-old male patient with ophthalmopathy due to vitreous opacities and positive family history for visual loss. As 22 patients were alive at the end of the study, we calculated the hATTR prevalence in Crete to be 35 cases per 1 million inhabitants. Discussion: Our study revealed that the prevalence of hATTR in Crete is one of the world's highest. Three different pathogenic TTR variants causing distinct clinical phenotypes were identified in this relatively small population pool.